Topologie-Optimierung eines radselektiv angesteuerten Fahrzeugs basierend auf einer optimalen Fahrzeugführungsregelung - Schwartz, Manuel (Karlsruher Beiträge zur Regelungs- und Steuerungstechnik, 2022)
The electrification and automation of passenger vehicles promote innovations of the entire vehicle architecture. If wheel-selective steered and driven vehicles are considered, challenges of urban regions can be met. In order to combine these development priorities with the alternative vehicle concept, an optimal suspension is designed for the vehicle concept. The topology optimization of a virtual wheel suspension takes place in interaction with a continuous, optimal dynamics vehicle control.